Penyuluhan Kesehatan Dan Pelaksanaan Suntik Sehat Ternak Sapi Sebagai Upaya Peningkatan Kesehatan Ternak Di Desa Sengkol : INTRODUCTION OBJECTIVES RESEARCH METHODS RESULTS DISCUSSION CONCLUSION - Raihan Nafila; Tia Lestari; Dwi Rachmat Septiawan; Ilham Shaomi; Fitrah Nurhidayah; Putri Andini; Ginda Ayu Saptari; Aulia Tsabita; Sadina Lubna; Nuriadi Nuriadi; Muhammad Rifqi Rajaburrobbani (Universitas Mataram, 2026)
The cattle farming sector plays a strategic role in improving the rural economy. However, low attention to livestock health is often a major obstacle to increasing cattle productivity. Sengkol Village, Pujut District, Central Lombok Regency, is an area with significant cattle farming potential, but still faces livestock health issues due to a lack of knowledge about health management and disease prevention. This Community Service Program (KKN) aims to increase livestock farmers' understanding and improve the health of their cattle through health education and health injections. The methods used include field observation, livestock health education, and hands-on practice of administering vitamins and deworming to cattle. The results of the activity indicate an increase in livestock farmers' knowledge and awareness of the importance of maintaining livestock health, as well as an improvement in livestock condition, as indicated by increased activity and appetite. This activity is expected to have a sustainable impact on improving the health and productivity of cattle in Sengkol Village.